'A presence in the community': developing innovative practice through realist evaluation of widening participation in West Yorkshire. (20th November 2020) - Formby, Adam; Woodhouse, Anna; Basham, Jemma; Roe, Francesca
This paper examines the role realist evaluation can play in supporting innovative practice in widening participation (WP) activity. Based on the Go Higher West Yorkshire Uni Connect project (formerly the National Collaborative Outreach Programme, or NCOP), a new model of WP provision has been developed to support learners in spatially disadvantaged communities where access to Higher Education is nationally less than average. It offers specific examples of innovative practice developing a locally tailored approach to WP activities based on community contexts. A realist evaluation framework is utilised to iteratively assess WP activity through subsequent development and modification of relevant programme theory. The article contributes to literature through offering a reflexive account of how realist evaluation can be utilised in terms of WP outreach.